Respuesta :
Answer:
x = 7
y = 0
Step-by-step explanation:
use substitution method:
2(-6y + 7) - 9y = 14
-12y + 14 - 9y = 14
-21y = 0
y = 0
x = -6(0) + 7
x = 7
Step-by-step explanation:
Hey there!
Given eqautions are;
2x-9y= 14……………(i)
x= -6y+7………………(ii)
~ Putting the value of"x" from eqaution (ii) in eqaution (i).
2(-6y+7) - 9y = 14
~ Simplify it.
-12y +14 -9y= 14
21y = 0
y =0/21
Therefore, y= 0.
Now,
~ Put value of "x" on eqaution (ii).
X = -6(0)+7
x= (0)+7
x= 7
Therefore, x= 7.
Check:
Putting the value of X and y in eqaution (ii)
7= -6(0)+7
7=7(True).
x= 7
y= 0
Hope it helps....